Laminar Organization of FM Direction Selectivity in the Primary Auditory Cortex of the Free-Tailed Bat - Macias, Silvio; Bakshi, Kushal; Smotherman, Michael (Frontiers in Neural Circuits, 2019)
We studied the columnar and layer-specific response properties of neurons in the primary auditory cortex (A1) of six (four females, two males) anesthetized free-tailed bats, Tadaridabrasiliensis, in response to pure tones and down and upward frequency modulated (FM; 50 kHz bandwidth) sweeps. In addition, we calculated current source density (CSD) to test whether lateral intracortical projections facilitate neuronal activation in response to FM echoes containing spectrally distant frequencies from the excitatory frequency response area (FRA). Auditory responses to a set of stimuli changing in frequency and level were recorded along 64 penetrations in the left A1 of six free-tailed bats. FRA shapes were consistent across the cortical depth within a column and there were no obvious differences in tuning properties. Generally, response latencies were shorter (<10 ms) for cortical depths between 500 and 600 μm, which might correspond to thalamocortical input layers IIIb–IV. Most units showed a stronger response to downward FM sweeps, and direction selectivity did not vary across cortical depth. CSD profiles calculated in response to the CF showed a current sink located at depths between 500 and 600 μm. Frequencies lower than the frequency range eliciting a spike response failed to evoke any visible current sink. Frequencies higher than the frequency range producing a spike response evoked layer IV sinks at longer latencies that increased with spectral distance. These data support the hypothesis that a progressive downward relay of spectral information spreads along the tonotopic axis of A1 via lateral connections, contributing to the neural processing of FM down sweeps used in biosonar.